DEVELOPMENT OF THE REPUBLICAN INFORMATION AND EDUCATIONAL ENVIRONMENT - D. A. Kachan; P. A. Lis; M. V. Mironchik (Цифровая трансформация)
The article is devoted to the formation of a modern educational space. The reasons for the phenomenon DIGITAL TRANSFORMATION, No 3 (4), 2018 47 of digitalization of the education system are analyzed. The characteristics of regulatory and legal provision in the field of information and communication technologies at the international level are given, problems of development and improvement of the quality of electronic educational resources are revealed. In addition, the article considers the structure of the information and educational environment created in the Republic of Belarus, including aspects that go beyond the didactics and management of educational processes. Developed proposals for improving the single information and educational environment, based on the principles of standardization and increased participation in the activities of international organizations.